Innovating Public Library Services: A Case Study of the M-Mobilib Development and Implementation - Hermawan, Hermawan (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This study analyzes the innovation process behind mobile library applications in regional public libraries, focusing on the stages of idea generation, adoption, and implementation. It also explores the factors that support or hinder the success of these technological innovations and evaluates the quality of services provided through such platforms. Using a descriptive qualitative approach and snowball sampling technique, data were collected through interviews, document analysis, and observations. The findings revealed that successful mobile library app development relies on a structured innovation process, including collaborative idea formulation, iterative adoption strategies, and adaptive implementation. Critical success factors included institutional support, user engagement, and technological readiness, while key barriers involve limited digital infrastructure, resistance to change, and inadequate technical skills. The study also underscores the necessity of assessing service quality as an integral part of evaluating mobile innovations. The case of M-Mobilib was presented as a best-practice example, demonstrating how mobile apps can effectively enhance public library services. Overall, this research contributes to the understanding of how digital innovations can expand access to information, stimulate service modernization in the public sector, and address disparities in digital access. Future research is encouraged to examine the long-term outcomes and scalability of mobile library applications across diverse contexts.